Analyzing the attitude of Indian citizens towards COVID-19 vaccine – A text analytics study. Issue 2 (March 2021) - Praveen, SV; Ittamalla, Rajesh; Deepak, Gerard
Abstract: Background and aims: The government of India recently planned to start the process of the mass vaccination program to end the COVID-19 crises. However, the process of vaccination was not made mandatory, and there are a lot of aspects that arise skepticism in the minds of common people regarding COVID-19 vaccines. This study using machine learning techniques analyzes the major concerns Indian citizens voice out about COVID-19 vaccines in social media. Methods: For this study, we have used social media posts as data. Using Python, we have scrapped the social media posts of Indian citizens discussing about the COVID- 19 vaccine. In Study 1, we performed a sentimental analysis to determine how the general perception of Indian citizens regarding the COVID-19 vaccine changes over different months of COVID-19 crises. In Study 2, we have performed topic modeling to understand the major issues that concern the general public regarding the COVID- 19 vaccine. Results: Our results have indicated that 47% of social media posts discussing vaccines were in a neutral tone, and nearly 17% of the social media posts discussing the COVID-19 vaccine were in a negative tone. Fear of health and allergic reactions towards the vaccine are the two prominent issues that concern Indian citizens regarding the COVID-19 vaccine. Conclusion: With the positive sentiments regarding vaccine is just over 35%, the Indian government needs to focus especially on addressing the fear of vaccines before implementing the process of mass vaccination. Highlights: Our results show that only 35% of social media posts (n = 73, 760) about COVID-19 vaccines were in a positive tone. As the number of COVID-19 cases increases, there is a rise in positive sentiments towards COVID-19 vaccines. Health and allergic reactions to the COVID-19 vaccine are the major concerns of Indian citizens about COVID-19 vaccines.